Novel Method for Electroless Etching of 6H–SiC - Károlyházy, Gyula (Nanomaterials (Basel), 2020)
In this article, we report an electroless method to fabricate porous hexagonal silicon carbide and hexagonal silicon carbide nanoparticles (NPs) as small as 1 nm using wet chemical stain etching. We observe quantum confinement effect for ultrasmall hexagonal SiC NPs in contrast to the cubic SiC NPs. We attribute this difference to the various surface terminations of the two polytypes of SiC NPs.